The Paris agent - Rimmer, Kelly (Graydon House, 2023)
"Twenty-five years after the end of the war, aging British secret operative Noah Ainsworth often thinks about the undercover SOE agent who saved his life when a mission went wrong during his perilous, exhilarating time in occupied France. A head injury sustained on his final operation has caused frustrating gaps in his memories, including information about the agent's identity and whether she even survived the war. Noah's daughter Charlotte begins a search for answers. What she uncovers is the stories of Fleur and Chloe, two otherwise ordinary women who are called up for secret deployment in France in 1943. Taking enormous risks with scant training, information and resources, the women have no idea they're at the mercy of a double agent. As Charlotte's search reveals long-overlooked clues about the traitor's identity, unsettling hints point close to home, and mysteries are unraveled about the dangerous, dramatic last days of the war that lead to Chloe's and Fleur's shocking fates."--Provided by publisher.